Evaluation of heavy metal uptake and translocation by Acacia mangium as a phytoremediator of copper contaminated soil - Nik Ab. Majid, Nik Muhamad; Islam, Md. Monirul; Justin, Veronica; Abdu, Arifin; Ahmadpour, Parisa (Academic Journals, 2011)
Many organic and inorganic pollutants, including heavy metals are being transported and mixed with the cultivated soils and water. Heavy metals are the most dangerous pollutants as they are nondegradable and accumulate and become toxic to plants and animals. An experiment was conducted in the glasshouse to evaluate the potential of Acacia mangium as a phytoremediator to absorb heavy metals from contaminated soils. A. mangium seedlings were planted in the growth media (soil + different levels of copper). The different levels of Cu were: T 0 (control, soil), T 1 (50 ppm Cu), T 2 (100 ppm Cu), T 3 (200 ppm Cu), T 4 (300 ppm Cu) and T 5 (400 ppm Cu). The highest growth performance such as basal diameter, height and number of leaves was in T 1. The highest biomass was recorded in T 1. Highest accumulation of Cu (93.55 ppm) and Zn (79.13 ppm) were recorded in T 5 while Cd (8.88 ppm) in T 3. Cu was highly concentrated in the roots, Cd was accumulated in the leaves and roots, whereas, Zn was in stems and leaves. A. mangium showed high translocation factor (TF) and low bioconcentration factor (BCF) values in soil at higher metal concentrations as well as it was able to tolerate and accumulate high concentrations of Cd, Cu and Zn. It may be concluded that this species can be a good efficient phtyoremediator for heavy metals (Cd, Cu and Zn) contaminated soils to mitigate soil pollution.